Purple-Dyed Textiles from Wadi Murabba’at: Historical, Archaeological and Chemical Aspects - Sukenik, Naama; Iluz, David; Shamir, Orit; Varvak, Alexander; Amar, Zohar (Archaeological Textiles Review, 2013)
This article presents three prestigious textiles dyes with murex shellfish, which were found in the Murabba’at Caves in the Judean Desert and are dated to the Roman Period. The textiles were analyzed using High Performance Liquid Chromatography (HPLC). The results of the analysis indicate that one textile was dyed using Hexaplex trunculus and its color tends to blue-greenish; apparently, the dye solution was exposed to the sun during the dyeing process. The other two textiles underwent a double dyeing process using the Hexaplex trunculus and the Armenian Cochineal insect dye in order to give the fabric a reddish purple color, which was indicative of high status. Such a combination has not been reported in the results of dye analysis of ancient Israel textiles. Furthermore, these finds are unusual and unique in the light of discoveries of other textiles from Israel dated to the Roman Period. According to the dye analysis and tests of different aspects of the purple textiles, we propose the origin of the textiles.